Analisis Sensitivitas Model Black-Litterman Menggunakan Treynor Ratio pada Portofolio Saham - Puja Ermiati; Devni Prima Sari (UNIVERSITAS NEGERI PADANG, 2022)
Investment is an activity that can not separate from return and risk, so that forming portfolio is important to risk minimizing and profit optimizing. One of way to optimizing portfolio is using Black-Litterman model. This model is model that combine equilibrium return by CAPM eith investor’s views about return an asset. Purpose of this research are to form Black-Litterman model with tau calibration and measure the best portfolio performance with treynor ratio. This research used secondary data stock in LQ-45 index during August 2019-January 2020. Selecting portfolio by selecting high return expected CAPM are CPIN, WIKA, ADRO and CTRI. Forming portfolio using Black-Litterman model by calibration so obtain the best measure performance by Treynor Ratio are 0,12142 with =1 and potfolio return 0,26445